Pre‐procedural arrhythmia burden and the outcome of catheter ablation of idiopathic premature ventricular complexes. Issue 4 (15th March 2021) - Asatryan, Babken; Seiler, Jens; Bourquin, Luc; Knecht, Sven; Servatius, Helge; Madaffari, Antonio; Baldinger, Samuel H.; Badertscher, Patrick; Küffer, Thomas; Spies, Florian; Tanner, Hildegard; Kühne, Michael; et al.
Abstract: Background: Radiofrequency catheter ablation of idiopathic premature ventricular complexes (PVCs) is an effective method for eliminating symptoms and preventing/reversing arrhythmia‐induced cardiomyopathy. One reason for procedural failure is low PVC frequency during the procedure. We aimed to investigate the relation between pre‐procedural PVC burden and outcome of idiopathic PVC catheter ablation. Methods: Patients who underwent idiopathic PVC ablation between 2013 and 2019 at two tertiary referral centers were retrospectively included. All procedures were performed using irrigated‐tip ablation catheters and a 3D electro‐anatomical mapping system. Sustained ablation success was defined as a ≥80% reduction of pre‐procedural PVC burden determined by 24h‐Holter at follow‐up. Results: Overall, 254 patients (median age 54 years [IQR 42–64]; 47% male) were enrolled. The median pre‐ablation PVC‐burden was 22% (IQR 11–31%), which was reduced to a post‐ablation PVC burden of 0.3% (IQR 0–4%) after a median of 90 days. Sustained ablation success was achieved in 182 patients (72%). Pre‐procedural PVC burden did not differ between patients with sustained ablation success and recurrence during follow‐up (median 21% vs. 22%, p  = .76). When assessed in pre‐ablation PVC‐burden groups of ≤5%, 6–15%, 16–30%, and ≥31%, sustained ablation success was achieved in 67%, 75%, 71%, and 72%, respectively, with no significant difference ( p  = .89). Sustained ablation outcome for PVC‐burden ≤5% versus >5% showed no difference either (67% vs. 72%, p  = .52). Conclusions: Pre‐procedural Holter‐determined PVC burden does not predict the outcome of idiopathic PVC ablation. Thus, catheter ablation may be a reasonable first choice also for patients with symptomatic yet rare PVCs.